The Urgency of Narcotics Law Certainty in Indonesia After the Ratification of the Single Convention for Medical Purposes - Aringga, Rino Dedi; Saputra, Agung Arafat (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
Judicial Review of Law Number 35 of 2009 concerning Narcotics in Indonesia is currently a step to reform the law on the use of narcotics, one of which is marijuana, so that it can be used for medical purposes. Not a few, patients with diseases who need alternative treatment using marijuana extracts must be hindered by regulations that bind Law Number 35 of 2009 concerning Narcotics. Indonesia adopted the results of The United Nation's Single Convention On Narcotic Drugs 1961 or (single convention) as a step to combat illicit trafficking and misuse of narcotics which was made into narcotics law in Indonesia which is contained in Law Number 35 of 2009 today. The purpose of this writing and research is so that the government and society can increase their concern for the rights of citizens in carrying out the constitutional mandate. As stated in Article 28 H of the 1945 Constitution, "Every person has the right to live in physical and spiritual prosperity, to have a place to live, and to receive protection from a good and healthy life and the right to obtain health services". The data collection technique used by researchers is library research, with qualitative methods, in order to contain the results of studies from collecting literacy data from literature and scientific journals. Therefore, the use of library research and qualitative methods in research can be used to analyze the results of the study and With this research, it will be studied to find legal reasons from the government in the case of medical marijuana in Indonesia. These problems will then be analyzed using analytical descriptive methods to find new concepts related to the legalization of medical marijuana in Indonesia. This study suggests that medical marijuana may have legal potential in the future. This urgency is also demonstrated by the political will of the Indonesian Ulema Council and the Ministry of Health. It is hoped that this research will provide recommendations regarding appropriate educational insights about medical marijuana and potential legalization in the future. Abstrak: Judicial Review Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika di Indonesia sampai saat ini menjadi langkah mereformasikan Undang-Undang tentang penggunaan narkotika salah satunya adalah marijuana agar dapat dimanfaatkan untuk keperluan medis. Tidak sedikit, pasien pengidap penyakit yang membutuhkan pengobatan alternatif menggunakan ekstrak marijuana ini harus terhalangi oleh peraturan yang mengikat pada Undang-Undang Nomor 35 tahun 2009 Tentang Narkotika. Indonesia mengadopsi hasil dari The United Nation’s Single Convention On Narcotic Drugs 1961 atau (konvensi tunggal) sebagai langkah pemberatasan peradaran gelap dan salah guna penggunaan narkotika yang dijadikan Undang- undang narkotika di Indonesia yang dimuat pada Undang-Undang Nomor 35 Tahun 2009 saat ini. Penulisan dan penelitian ini bertujuan agar pemerintah dan masyarakat dapat lebih meningkatkan kepeduliannya terhadap hak warga negara dalam menjalani amanat konstitusional. Sebagaimana termaktub dalam Pasal 28 H Undang-Undang Dasar Tahun 1945, bahwa “Setiap orang berhak hidup sejahtera lahir dan batin, bertempat tinggal, dan mendapatkan perlindungan hidup yang baik dan sehat serta berhak memperoleh pelayanan kesehatan”. Teknik pengumpulan data yang digunakan peneliti adalah library research, denagn metode kualitatif, agar dapat memuat hasil studi dari pengumpulan data-data literasi dari kepustakaan maupun jurnal ilmiah. Oleh karenanya, penggunaan metode library research dan kualitatif dalam penelitian dapat menghasilkan kajian atas suatu fenomena dan yang lebih komprehensif dan Dengan penelitian ini akan dikaji untuk menemukan alasan hukum dari pemerintah dalam kasus ganja medis di Indonesia. Masalah-masalah tersebut kemudian akan dianalisis menggunakan metode deskriptif analitis dengan untuk menemukan konsep-konsep baru terkait legalisasi ganja medis di Indonesia. Studi ini menunjukkan bahwa ganja medis akan mungkin memiliki potensi legal di masa depan. Urgensi ini juga didemonstrasikan oleh kemauan politik Majelis Ulama Indonesia dan Kementerian Kesehatan. Dari penelitian ini diharapkan akan memberikan rekomendasi terkait wawasan pendidikan yang tepat tentang ganja medis dan potensi legalisasi di masa depan.